1997
DOI: 10.1902/jop.1997.68.7.613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Topical Metronidazole and Mechanical Treatment on the Subgingival Flora in Deep Periodontal Pockets in Cuspids and Bicuspids

Abstract: The Effect on the subgingival microflora of a single topical administration of a 95% collagen and 5% metronidazole device in combination with debridement was investigated in 30 adult periodontitis patients in comparison with mechanical treatment alone. For each patient, plaque samples from test and control sites in cuspids and bicuspids were collected for culture and enumeration of total anaerobically cultivable bacteria (TA), black-pigmented anaerobes (BPA), and Actinobacillus actinomycetemcomitans (Aa). Spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…[1213] The disadvantage with these systems was that they were nonresorbable and had to be removed. In this study, we have used resorbable collagen fibers loaded with 2 mg tetracycline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1213] The disadvantage with these systems was that they were nonresorbable and had to be removed. In this study, we have used resorbable collagen fibers loaded with 2 mg tetracycline.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with earlier studies where clinical and microbiological parameters were evaluated to assess the effect of local metronidazole therapy and significant changes were reported in all the parameters. [1213] In the present study, we had put up multiplex PCR using primers for Aa, Pg, and Tf, as described in an earlier study. [29] An earlier study carried out by Garcia et al described the procedure for identification of Aa, Pg, and Prevotella intermedia using multiplex PCR.…”
Section: Discussionmentioning
confidence: 99%
“…A combined mechanical and systemic antibiotic therapy has, in numerous studies, proved to be more successful than mechanical therapy alone (Slots et al 1986, Goodson 1994, Van Winkelhoff et al 1996, Berglundh et al 1998, Tinoco et al 1998, Winkel et al 1998, Flemmig et al 1998). But even though these studies have shown the effectiveness of an adjunct antibiotic therapy, it was impossible to eliminate all the putative periodontal pathogens such as A. actinomycetemcomitans , P. gingivalis and P. intermedia out of the periodontal pockets respectively out of the oral cavity in every patient (Slots & Rosling 1983, Loesche et al 1984, Gusberti et al 1988, Pedrazzoli et al 1992, Hitzig et al 1997, Winkel at al. 1998, Tinoco et al 1998, Flemmig et al 1998, Wong et al 1999, Feres et al 1999, Riep et al 1999, Buchmann et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Different drugs used for local delivery are tetracyclines, including doxycycline[16] and minocycline,[7] metronidazole[89] and chlorhexidine. [10–14] Of all the chemical plaque control agents, chlorhexidine has proven to be the most effective, safe and clinically effective in reducing plaque and gingivitis and is the time-tested gold standard for the treatment of periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%